1997
DOI: 10.1523/jneurosci.17-14-05357.1997
|View full text |Cite
|
Sign up to set email alerts
|

Postsynaptic Inhibitors of Calcium/Calmodulin-Dependent Protein Kinase Type II Block Induction But Not Maintenance of Pairing-Induced Long-Term Potentiation

Abstract: The role of postsynaptic kinases in the induction and maintenance of long-term potentiation (LTP) was studied in the CA1 region of the rat hippocampal slice. A peptide inhibitor for the catalytic domain of calcium/calmodulin-dependent protein kinase type II (CaM-kinase) was applied through a perfused patch pipette. The inhibitor completely blocked both the shortterm potentiation and LTP induced by a pairing protocol. This indicates that the kinase or kinases affected by the peptide are downstream from depolari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
148
2
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 191 publications
(159 citation statements)
references
References 72 publications
(98 reference statements)
6
148
2
3
Order By: Relevance
“…Acute hippocampal slices were prepared from 17-21-day-old Long-Evans rats according to the methods described by Otmakhov et al(1997). Rats were decapitated under anesthesia (5% urethane).…”
Section: Slice Preparationmentioning
confidence: 99%
See 3 more Smart Citations
“…Acute hippocampal slices were prepared from 17-21-day-old Long-Evans rats according to the methods described by Otmakhov et al(1997). Rats were decapitated under anesthesia (5% urethane).…”
Section: Slice Preparationmentioning
confidence: 99%
“…To investigate possible other effects of D-890 that might impair LTP, we tested the effect of the drug on a molecule that is known to be required for pairing-induced LTP induction, CaMKII (Otmakhov et al, 1997). These tests were performed by the laboratory of Thomas Soderling and showed that the drug inhibited CaMKII activity in vitro.…”
Section: D-890 Inhibits Camkii Activity At High Concentrationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, once activated, CaMKII can transition into a Ca 2+ /CaM-independent, hyper-activated state via the autophosphorylation of neighboring enzymatic subunits (Hanson et al 1994; Rich and Schulman 1998), and thus continue to phosphorylate its substrates even after the plasticity-inducing Ca 2+ signal has ended (Saitoh and Schwartz 1985;Miller and Kenney 1986;Lou et al 1986;Yang and Schulman 1999). Third, suppression of CaM-KII using chemical antagonists blocks all known forms of NMDA receptor-dependent long-term potentiation (LTP) (Malinow et al 1989;Fukunaga et al 1993;Pettit et al 1994;Lledo 1995;Barria et al 1997b;Otmakhov et al 1997;Malenka and Bear 2004).…”
Section: Introductionmentioning
confidence: 99%